Media and the electoral process in Malaysia / Dr. Baharuddin Aziz and Sankaran Ramanathan - Aziz, Baharuddin (Dr.); Ramanathan, Sankaran (Faculty of Communication and Media Studies (FCMS), 1994)
The Malaysian general elections of October 1990 was noticeably different from the six previous general elections held in Malaysia since 1963 (in 1964, 1969, 1974, 1978, 1982, and 1986).